2016
DOI: 10.17221/786/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

Use of terraces to mitigate the impacts of overland flow and erosion on a catchment

Abstract: The paper presents the impact of a historical system of terraces constructed centuries ago to mitigate the effect of a steep slope on overland flow. Systems of this type were constructed in past centuries by land owners, who then ploughed the land and grew crops on it. They used stones collected from the local agricultural fields as their terracing material. The influence of terraces on overland flow was simulated using the KINFIL. The overland flow is therefore reduced by greater infiltration of extreme rainf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…These results are in line with observations in many other parts of the world (Di Lazzaro et al, 2015;Wei et al, 2016). For example, Kovář et al (2016) found similar effects of agricultural terraces on storm runoff on a similar-sized hillslope in Bohemia (Czech Republic); however, they used the kinematic wave approximation to route storm flow because of lower rainfall intensities and a possibly greater relative contribution from subsurface flow compared to Mediterranean and semi-arid watersheds. Fig.…”
Section: Wfiuh and The Evaluation Of Ecosystem Servicessupporting
confidence: 88%
“…These results are in line with observations in many other parts of the world (Di Lazzaro et al, 2015;Wei et al, 2016). For example, Kovář et al (2016) found similar effects of agricultural terraces on storm runoff on a similar-sized hillslope in Bohemia (Czech Republic); however, they used the kinematic wave approximation to route storm flow because of lower rainfall intensities and a possibly greater relative contribution from subsurface flow compared to Mediterranean and semi-arid watersheds. Fig.…”
Section: Wfiuh and The Evaluation Of Ecosystem Servicessupporting
confidence: 88%
“…The preference for large stones can explain the low occurrence of large boulders in the deforested catchment compared with the forested catchment. Selective removal of boulders is also a common stone‐clearing technique used for cultivation in other regions with karst relief or affected by freeze action (Andriani & Walsh, ; Gams, Nicod, Julian, Anthony, & Sauro, ; Kovář, Bačinová, Loula, & Fedorova, ). Rock extraction decreased the boulder areas to only 8.1% of catchment area in the deforested catchment compared with 30% of the forested catchment and gained new land for agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…(6) expresses the Green-Ampt theory (Rawls & Brakensiek 1983), the left side describes the Darcy concept for the process of infiltration v f (t). K s is the hydraulic conductivity (m/s), H f is the capillary suction on the infiltration front (m), is the difference between the saturated soil moisture content and actual content (-), z f is the depth of the infiltration front (m), and z is the vertical ordinate (m) (Kovář et al 2016).…”
Section: Methodsmentioning
confidence: 99%